PRELIM - UTHM, penerbit (Journal of Techno-Social, 2015)
1. PATRONAGE 2. SCIENTIFIC ADVISORY BOARD 3. EDITORIAL BOARD 4. ASSOCIATE EDITOR 5. EDITORIAL MANAGEMENT COMMITTEE 6. MESSAGE FROM EDITOR IN CHIEF 7. CONTENTS